Assessing the impact of virtual learning on family medicine trainees’ medical knowledge using progress tests: a retrospective cohort study - Karina Prucnal; Stuart Murdoch; Kulamakan Kulasegaram; Fok-Han Leung (Canadian Medical Education Journal)
Background: Progress testing provides residents with an opportunity to identify strengths and weaknesses, encouraging self-directed learning. The University of Toronto’s Department of Family & Community Medicine administers the Family Medicine Mandatory Assessment of Progress (FM-MAP) biannually to track resident competency and medical knowledge. Our aim was to determine the impact of virtual learning on Family Medicine residents.